2019
DOI: 10.1111/jpn.13250
|View full text |Cite
|
Sign up to set email alerts
|

Influence of elevated protein and tannin‐rich peanut skin supplementation on growth performance, blood metabolites, carcass traits and immune‐related gene expression of grazing meat goats

Abstract: The aim of the present study was to define whether elevated rumen-undegradable protein (RUP) and tannin-rich peanut skin (PS) supplementation would affect animal growth performance, average daily gain (ADG), blood metabolites, carcass traits associated with lipogenic and immune-related gene expressions in meat goats grazing winter wheat (WW). Thirty-six Kiko-crossbreed male goats at approximately 6 months of age were blocked by body weight (BW; 25.6 ± 1.1 kg) and randomly assigned to one of the four treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…To the best of our knowledge, amino acids are mainly absorbed in the small intestine, so protein passing through rumen has become an important research direction for amino acid metabolism [44]. Tannins are widely reported to reduce rumen BH, protect rumen protein degradation and reduce methane production [8,45,46]. However, paper mulberry rich in tannins did not generate the expected results in amino acids of LD, probably because silage reduced the tannin content.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, amino acids are mainly absorbed in the small intestine, so protein passing through rumen has become an important research direction for amino acid metabolism [44]. Tannins are widely reported to reduce rumen BH, protect rumen protein degradation and reduce methane production [8,45,46]. However, paper mulberry rich in tannins did not generate the expected results in amino acids of LD, probably because silage reduced the tannin content.…”
Section: Discussionmentioning
confidence: 99%
“… Sources : Bezerra et al (2016), Casas et al (2018), Chakeredza et al (2002), Correia, de Carvalho, Oliveira, Pires, Ribeiro, Silva, Leão & Oliveira (2016), Correia, de Carvalho, Oliveira, Pires, Ribeiro, Silva, Leão, Simionato, et al (2016), Eckert et al (2010), el Boushy and Raterink (1989), Fernandes et al (2013), Grosso et al (2000), Hill et al (1986a, 1986b, 1987), Li et al (2014), McBrayer et al (1983), Min et al (2020), Min, Frank et al (2019), National Research Council (1989), Saito et al (2016), Schnaider et al (2014), Silva, de Medeiros et al (2016), Silva, Oliveira et al (2016), Staples et al (1997), and Vasco et al (2021). …”
Section: Plants Of the Arachis Genus As Forage Cropsmentioning
confidence: 99%
“…Goats fed on alfalfa with peanut skin showed reduced plasma oxidative stress markers and malondialdehyde compared to alfalfa alone, indicating that peanut skins have antioxidant properties and can be included in goat diets (Saito et al, 2016). In vitro rumen fermentation experiments showed that peanut skins affect the population of ruminal methanogens and suppress methanogenesis (Min et al, 2020). Partially replacing alfalfa with peanut skins improved the average daily gain and changed lipogenic and immune‐related gene expression of goats.…”
Section: The Forage Value Of Cultivated Peanutmentioning
confidence: 99%
See 1 more Smart Citation